2018
DOI: 10.3906/sag-1707-147
|View full text |Cite
|
Sign up to set email alerts
|

e association of neuropathic pain and disease activity, functional level, and quality of life in patients with ankylosing spondylitis: a cross-sectional study

Abstract: Background/aim: Increased neuropathic pain (NP) symptoms are seen in rheumatologic diseases such as fibromyalgia, osteoarthritis, and rheumatoid arthritis, but no studies have demonstrated a relationship between ankylosing spondylitis (AS) and NP except for a brain imaging study. The aim of this study was to estimate the presence of NP in patients with AS and to investigate how NP was related to disease activity, functional status, and quality of life.Materials and methods: A total of 100 AS patients (71 males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
(50 reference statements)
2
9
0
Order By: Relevance
“…Previous studies, either in RA or SpA, showed that high painDETECT scores were generally not associated with greater inflammation (C-reactive protein and erythrocyte sedimentation rate) but strongly correlated with the patients' global assessment. 14 This was also true for our cohort ( P = 0.000).…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies, either in RA or SpA, showed that high painDETECT scores were generally not associated with greater inflammation (C-reactive protein and erythrocyte sedimentation rate) but strongly correlated with the patients' global assessment. 14 This was also true for our cohort ( P = 0.000).…”
Section: Discussionsupporting
confidence: 74%
“…The present study showed that 23.4% of the patients with axSpA had NP, which is slightly higher than previous studies. [ 12 , 13 , 15 ] Patients with no pain relief reported higher rates of NP, and the presence of NP predicts poor pain relief in axSpA patients treated with NSAIDs. Of note, NSAIDs reduce the sensitivity of local pain receptors to inflammatory substances by blocking cyclooxygenase, interfering with prostaglandin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…This form was designed by the researchers based on the relevant literature. Items consisted of questions about demographic characteristics and physical, social, and psychological effects associated with AS (age, sex, marital status, education level, employment, reason for not working, regular health control, medication, exercise, patient expression about physical status, social life, psychological state, and sexual life; Duruöz et al, 2013; Geler-Külcü et al, 2018; Hamilton-West & Quine, 2009; Kotsis et al, 2014; Lu et al, 2019).…”
Section: Methodsmentioning
confidence: 99%